Competitive Strategies between Formula 1 Manufacturers in the Global Mass-Market for Road Cars - Robinson, Mark Edward (2007)
This paper employs qualitative secondary source analysis to examine competitive strategies between those road car manufacturers that are also Formula 1 engine manufacturers. Particular emphasis is placed on Porter's (1980) generic strategies, the resource-based view, and the role of corporate culture and brand reputation. The external market in which these firms compete is examined. Then the internal, historical strategic development of each of the firms is reviewed. This allows future strategic recommendations to be proposed for each firm. Findings stress the importance of responding to the need for low emissions vehicles, the external threat of the large Asia-Pacific firms, and the importance of fostering a company's brand reputation.